LAW ENFORCEMENT ON ENVIRONMENTAL PROTECTION AND RESOURCE CONSERVATION - Jeanne Darc Noviayanti Manik; Wirazilmustaan Wirazilmustaan (PROGRESIF: Jurnal Hukum, 2019)
Conservation of natural resources is a natural resource management whose utilization is done wisely to ensure the continuity of its availability by maintaining and improving the quality of diversity and value. Conservation of natural resources and ecosystems aims to achieve the realization of the sustainability of natural resources and the equilibrium of the ecosystem so that it can better support the efforts to improve the community welfare and the quality of human life. The problem are the implementation of conservation of natural resources and its ecosystem in the region based on Act No. 5 of 1990 and law enforcement against perpetrators of the conservation of natural resources and ecosystems. The research method used is legal research using a statutory and conceptual approach. The conservation of natural resources and ecosystems is based on preserving the ability and utilization of natural resources and their ecosystem in a harmonious and balanced environment. The conservation of natural resources and ecosystems is conducted through the protection of life-supporting systems, preserving the diversity of plant and animal species along with its ecosystem and the sustainable utilization of natural resources and ecosystem.